The Potential Development of self-care in Elderly with Hypertension to Prevent Complication in Thongchainau Sub-District, Pakthongchai District, Nakhon Ratchasima Province - งอนสำโรง, ชลลดา; สละวงษ์ลักษณ์, ทองทิพย์ (Ratchaphruek Journal, 2019)
This action research aimed to develop the potential in elderly with hypertension in Thongchainau Sub-District, Pakthongchai District, Nakhon Ratchasima Province. The study was divided into three phases; 1) studying of community context and strategy,2)processes of potential development, and 3)studying of the results on elderly with hypertension potential development. The sample groups were 31 elderly people with hypertension. Data were collected via observation, questionnaire and records and subsequently analyzed using statistics, frequency distribution, percentage, minimum, maximum, standard deviation, and Paired t-test. The contextual result revealed that: Ban Nong-Danchang was aged society with a 39.17% hypertension rate. Community support and participation in the health care of the elderly, but also not aware of self-care before complications from hypertension. In aspect of elderly people with hypertension potential development, There were three activity plans, which comprised of workshop training by Protection Motivation Theory application program, home visits and knowledge sharing, at a total of 70 hours. It was found that elderly people with hypertension completely participated in action plan consisted of planning, action, observation and reflection. In aspect of developmental result, it was found that the sample group had knowledge, perceived severity, perceived probability, self-efficacy and response efficacy. Moreover, they behaved according the 3E principle (eat, exercise and emotion) more, higher with statistically at the level of 0.05 had decreased blood pressure level.